Thermal performance enhancement of an evacuated tube solar collector using graphene nanoplatelets nanofluid - Iranmanesh, S.; Ong, H.C.; Ang, B.C.; Sadeghinezhad, E.; Esmaeilzadeh, A.; Mehrali, M. (Elsevier, 2017)
In this study, the effect of graphene nanoplatelets (GNP)/distilled water nanofluid on the thermal performance of evacuated tube solar collector (ETSC) water heater was experimentally investigated. The mass percentage of GNP was considered at 0.025, 0.5, 0.075 and 0.1 wt%. The physical and thermal properties of the GNP nanofluids including stability, specific heat capacity, viscosity and thermal conductivity were investigated. The thermal efficiency tests on the solar collector were carried out for varying volumetric flow rate of 0.5, 0.1, and 1.5 L/min while the ASHRAE standard 93–2003 was considered to calculate the efficiency of the collector. The results indicated that the solar collector thermal efficiency gave enhancement up to 90.7% at a flow rate of 1.5 L/min when the GNP nanofluid was used as an absorption medium. The results indicated that by increasing the mass percentage of nanoparticles, thermal energy gain also increases, reaching a higher outlet temperature of the fluid when graphene nanosheets are used.